1988
DOI: 10.1111/j.1445-2197.1988.tb01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Eeg Monitoring During Carotid Endarterectomy

Abstract: One hundred and thirty‐one patients undergoing 142 carotid endarterectomy procedures were randomized to have their operation performed either with or without intra‐operative electroencephalographic (EEG) monitoring. Patients with EEG monitoring were shunted if both the internal carotid back pressure (ICBP) was less than 50 mmHg and ipsilateral change was evident on the EEG after clamping. Patients without EEG monitoring were shunted if ICBP was less than 50 mmHg. There was one postoperative death (0.7%) with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…10 The treatment groups were comparable, but the method of randomization, blinding of outcome assessment, and duration of follow-up were unclear. Three of 72 (4.1%) patients in the combined monitoring group had ipsilateral strokes within 24 hours of surgery compared with 2 out of 70 (2.9%) in the stump pressure alone group (ORϭ1.47, 95% CIϭ0.25 to 8.68, Pϭ0.7).…”
Section: Resultsmentioning
confidence: 99%
“…10 The treatment groups were comparable, but the method of randomization, blinding of outcome assessment, and duration of follow-up were unclear. Three of 72 (4.1%) patients in the combined monitoring group had ipsilateral strokes within 24 hours of surgery compared with 2 out of 70 (2.9%) in the stump pressure alone group (ORϭ1.47, 95% CIϭ0.25 to 8.68, Pϭ0.7).…”
Section: Resultsmentioning
confidence: 99%
“…34 They also cite the advantage of shunting in helping carotid artery closure. 7,10,29 Because most patients undergoing carotid surgery do not require a shunt to maintain adequate cerebral perfusion, the use of selective shunting has been advocated.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,16,17,[19][20][21] Some surgeons also believe that shunting aids in closure of the carotid arteries, whereas others believe the presence of shunt makes closure more difficult. 7,10,29 It has also been suggested that for those surgeons who use shunts only selectively, the relative infrequent use of the shunt makes its use more hazardous than with experienced surgeons.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…7 The treatment groups were comparable, but the method of randomization, blinding of outcome assessment, and duration of follow-up were unclear. Three of 72 patients in the combined monitoring group had ipsilateral strokes …”
Section: Resultsmentioning
confidence: 99%